2015
DOI: 10.1002/anie.201508746
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Carbazole Alkaloids by Ring‐Closing Metathesis and Ring Rearrangement–Aromatization

Abstract: Aprocess for the assembly of carbazole alkaloids has been developed on the basis of ring-closing metathesis (RCM) and ringrearrangement-aromatization (RRA) as the key steps. This method is based on allyl Grignard addition to isatin derivatives to provide smooth access to 2,2-diallyl 3-oxindole derivatives through a 1,2-allyl shift. The diallyl derivatives were used as RCM precursors to afford a novel class of spirocyclopentene-3-oxindole derivatives, which underwent a novel RRA reaction to afford carbazole der… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(44 citation statements)
references
References 82 publications
3
41
0
Order By: Relevance
“…As expected, the use of allylation catalyst Ru‐1 led to the formation of corresponding diallylated pseudoindoxyls 7 in 55–98 % yield (Scheme ). Rapid screening of the reaction conditions demonstrated that the Hoveyda–Grubbs II precatalyst allowed the formation of the tricyclic adducts in up to 84 % yield . Owing to the rigid structure of the tricyclic adducts, diastereoisomers of 8 ab , 8 ac , and 8 ae were easily separated after isolation by column chromatography.…”
Section: Resultsmentioning
confidence: 71%
“…As expected, the use of allylation catalyst Ru‐1 led to the formation of corresponding diallylated pseudoindoxyls 7 in 55–98 % yield (Scheme ). Rapid screening of the reaction conditions demonstrated that the Hoveyda–Grubbs II precatalyst allowed the formation of the tricyclic adducts in up to 84 % yield . Owing to the rigid structure of the tricyclic adducts, diastereoisomers of 8 ab , 8 ac , and 8 ae were easily separated after isolation by column chromatography.…”
Section: Resultsmentioning
confidence: 71%
“…Unless otherwise noted, analytical grade solvents and commercially available reagents were used without further purification. N-protected isatins 1 (GP-1) 16 : N-alkylated isatin derivatives were prepared from commercially available isatins with different alkyl halides in the presence of K2CO3 in DMF at room temperature. MeI or BnBr (10.2 mmol, 3.0 equiv) was added to a stirred solution of isatin (3.4 mmol, 1.0 equiv) and K2CO3 (8.5 mmol, 2.5 equiv) in DMF and stirred for 12 h at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…[42,43] approach, Dash et al obtained 1 by ac opper(II) chloride-catalyzed coupling of 14. [46] In our originalp ublication, 2-hydroxy-3-methylcarbazole (14)w as synthesized by reactiono ft he arylamine 13 with ac yclohexadienylmolybdenum salt followed by oxidative cyclization and cleavage of the methyl ether. [25] Since then, variouss ynthetic approaches to 14 have been developed.…”
Section: Introductionmentioning
confidence: 99%
“…[25] Since then, variouss ynthetic approaches to 14 have been developed. [10,18,[46][47][48][49] Our approach using aB uchwald-Hartwig coupling of the aniline 13 and iodobenzene followed by palladium(II)-catalyzed oxidative cyclization and methyl ether cleavage provided 2-hydroxy-3-methylcarbazole (14)i nt hree steps and 85 %o verall yield on gram scale. [40,48,49] Using 14 as model compound, we screened the performance of variousr eagents for the oxidative coupling to the 1,1'-bicarbazole 1 ( Table 1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation